Spectrophotometric Estimation of Glimepiride from Pharmaceutical Dosage Forms - Ravindra, N.; Singhvi, I. (Asian Journal of Chemistry, 2010)
Two simple and sensitive visible spectrophotometric methods have been developed for the quantitative estimation of glimepiride from its tablet formulation. The developed methods are based on formation of chloroform extractable coloured complex of drug with methylene blue and safranine. The chloroform extracted complex of drug with methylene blue showed absorbance maxima at 652 nm and linearity was observed in the concentration range of 15-50 μg/mL (method-I), with safranine showed absorbance maxima at 536 nm and linearity was observed in the concentration range of 10-80 μg/mL (method-II). Results of analysis for both the developed methods were validated statistically and by recovery studies.